Perbedaan Bahasa Indonesia dan Bahasa Minang Antara Pria dan Wanita - Febriana, Noni; Alhusna, Asma; Anggraini, Dian; Gusta, Wienda (Fakultas Sastra Universitas Ekasakti, 2024)
Language is a verbal communication tool. Humans use language to communicate with each other. Language, like other social behavior, also accommodates gender differences. This research aims to analyze the language commonly used by male and female speakers of Indonesian and Minang in everyday life. The respondents were UPI 'YPTK' Padang undergraduate students. The data collected is in the form of words or texts which are then processed and presented in descriptive form. The collected data is then categorized and analyzed. From observations it can be seen that the language of men and women is different in several aspects, including in the choice of topics, vocabulary and grammar. These vocabulary differences include the use of adjectives, adverbs, enhancers, and the color of certain words. Meanwhile, in grammar, the difference lies in the use of question tags, hedges, and hyper correct grammar.